Pelayanan Administrasi Kesiswaan: Kunci Meningkatkan Kepuasan Siswa di SMA Swasta HKBP Lintongnihuta - Ramena Sinambela; Ruslan Juliana Pardosi; Tetti Manullang; Justice Z.Z Panggabean; Betty A.S Pakpahan (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
The purpose of this study was to determine the Effect of Student Administration Services on Student Satisfaction at HKBP Lintongnihuta Private High School. The method used in this study is a quantitative research method with inferential statistics. The population is all students of HKBP Lintongnihuta Private High School in the 2024/2025 academic year totaling 250 people and a sample of 65 people was determined using a random sampling technique. Data were collected with a closed questionnaire of 40 items. From the validity test, rxy was obtained for the X variable questionnaire, namely items number 1 to item number 27, it is known that 25 items are valid because r count is (between 0.407 and 0.766)> r table = 0.312, and it is known that 2 questionnaire items are invalid, namely questionnaires number 12 and number 17 because r count is (between 0.180 and 0.306) < r table = 0.312. Meanwhile, the validity test obtained rxy for the Y variable questionnaire, namely items number 28 to item number 42, it was found that 15 items were valid because r count was (between 0.402 to 0.834) > r table = 0.312. The results of data analysis show that student administration services have a positive effect on student satisfaction at HKBP Lintongnihuta Private High School, as evidenced by the following data analysis: 1) Analysis requirement test: a) positive influence test obtained rxy value = 0.633> rtable ( = 0.05, n = 65) = 0.244 thus it is known that there is a positive influence between variable X and variable Y. b) Significant relationship test obtained tcount value = 6.485> ttable ( = 0.05, dk = n-2 = 63) = 2.000 thus there is a significant relationship between variable X and variable Y. 2) Influence test: a) Regression equation test, obtained regression equation Y ̂="14","207"+0.460X. b) Regression determination coefficient test (r2) = 40%. 3) Hypothesis testing using the F test obtained Fcount > Ftable, namely 42.061 > 4.00. Thus Ha is accepted and H0 is rejected. It can be concluded that student administration services have a positive and significant effect on student satisfaction at HKBP Lintongnihuta Private High School.